Pengaruh Faktor Promosi, Pelayanan, Produk, dan Suku Bunga Terhadap Minat Menabung Mahasiswa Pada Bank Umum ( Studi Kasus BNI 46) - Kadek Adi Putra Gunawan; A. A. Sri Purnami; Nyoman Senimantara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
The purpose of this study was to determine the effect of promotion, service, product, and interest rates on students' interest in saving at a commercial bank. The data analysis technique used is multiple linear regression test, classic assumption test, determination test (R2), t test and F test. The results of this study show Y = 2.547 + 0.152 X1 + 0.088 X2 + 0.460 X3 + 0.345 X4 + e. The t test results showed that partially the Promotion, Service, Product, and Interest Rates variables had a positive and significant impact on students' interest in saving at a commercial bank. From the results of the F test shows that the variables of Promotion, Service, Products, and Interest Rates simultaneously have a significant effect on students' interest in saving at a commercial bank.